Impact of language barriers on access to healthcare for official language minority Francophones in Canada - de Moissac, Danielle; Bowen, Sarah (Healthcare management forum, 2017)
While there is strong international evidence that language barriers present obstacles to healthcare access, quality and safety, little research has been conducted on the experience of official language minorities in Canada. This multiple method research used on-line and paper-based surveys, combined with semi-structured individual interviews to explore the experience with access to care of Francophone minorities living in four Canadian provinces. The majority of Francophones surveyed reported limited access to French language services and described an environment where low importance is given to addressing language barriers within the health system. Even when services are available, the lack of services in French sometimes results in avoidance of care. Results confirm that many Francophones face similar barriers to care as other language minorities in Canada. Strategies to improve access for official language minorities are discussed.

Balises-Modèles de services d'interprétariat et d'accompagnement pour faciliter l'accès aux services de santé des communautés francophones et acadiennes vivant en situation minoritaire (INTACC) - sarah, Bowen; Richard, Lise; Chartier, renée (2016)
Ces balises ont été développés afin de guider les pourvoyeurs de services avec la compréhension des compétences, rôles, responsabilités et limites des services d’interprétariat et d’accompagnement, et étale les Principes éthiques de l’interprète. Ce document fut préparé dans le cadre du projet INTACC de la Société Santé en français par Dr Sarah Bowen, Renée

GUIDELINES - Interpreting and companion serivces models to facilitate access to health services for Francophone and Acadian minoritycommunities (INTACC) - Bowen, sarah; Renée, Chartier; Richard, Lise (2016)
These guidelines were written as a guide for service providers to gain an understanding of the competencies, roles, responsibilities, and limits of interpretation and accompaniment services. They also lay out an Interpreters’ Code of Ethics. The document was prepared for the Société Santé en français’ INTACC